Anti-Inflammatory Potential of Active Compounds in Moringa Leaves (Moringa Oleifera) Against Osteoarthritis Through in Silico Methods - William Braven Jaurie; Youla Annatje Assa; Diana Shintawati Purwanto (Eduvest - Journal of Universal Studies, 2026)
Osteoarthritis (OA) is a degenerative joint disease with a high global burden. Available therapies remain palliative, and selective COX-2 inhibition risks shifting arachidonic acid metabolism to the 5-lipoxygenase (5-LOX) pathway, which increases proinflammatory leukotrienes. Furthermore, no approved 5-LOX inhibitors exist for OA. This study aims to analyze the anti-inflammatory potential of active metabolites in moringa leaves as 5-LOX inhibitors in osteoarthritis using in silico methods. This study was conducted using in silico methods, including preparation of ligand and target protein structures, identification of binding sites, docking validation, molecular docking, and visualization of molecular interactions. Molecular docking was performed using AutoDock Vina software via PyRx to evaluate binding energy (ΔG). All moringa leaf metabolites bound stably to both the orthosteric and allosteric pockets of 5-LOX, with binding affinities competitive with those of the reference ligands particularly ellagic acid (ΔG = −7.7 kcal/mol) at the orthosteric site and isorhamnetin (ΔG = −8.3 kcal/mol) at the allosteric site. Docking validation confirmed the reliability of the method, supporting the feasibility of active metabolite compounds from moringa leaves as potential 5-LOX inhibitor candidates in osteoarthritis. Active metabolites of moringa leaves show potential as 5-LOX inhibitors with competitive affinity at orthosteric and allosteric sites, and may thus be developed as complementary anti-inflammatory agent candidates in osteoarthritis. However, further validation through in vitro and in vivo testing is required.